Embedded research in rehabilitation engineering. (1st September 2020) - Foord, David J. A.; Kyberd, Peter
Abstract : We examine concepts of new knowledge creation and embedded research in a case study on the i-limb, the world's first commercial prosthetic hand with five independently powered digits. Although the case demonstrates many elements of the mode 2 concept, that does not adequately describe the influence of context. In addition to the forces of contextualization, we argue there was also a strong influence on the R&D process and product from the embedding of scientific research and technology development in a location of use, specifically a prosthetic clinic in a hospital. We use the literature on embedded research to supplement our examination of this case of new knowledge creation. We contribute to the literature on mode 2 knowledge production and contexts of application by applying the literature on embedded research to explain the creation of new knowledge in locations of use.